Propuesta de intervención arquitectónica y paisajística en el eje natural compuesto desde la comunidad de Releche hasta la laguna amarilla, parroquia la Candelaria. - Caiza Rojas, Mateo Andres (2024)
The objective of this study was to raise an intervention proposal in the natural axis towards the Laguna Amarilla, located in El Altar volcano, parish of La Candelaria in the Penipe canton, where through this intervention strategic points were created that include an infrastructure in accordance with the landscape and thus stimulate activity in the area. Sangay National Park is a reserve with three snow-capped mountains in its territory, one of them is El Altar, whose entrance has two tourist trails, one from the parish of Quimiag/Riobamba and the other starting from the community of Releche, which was the subject of study in this research. The route has 13km considered as natural space, which to a certain extent have not been intervened by humans and are composed of geomorphological elements and atmospheric conditions that allow the development of plant and animal species. Understanding the importance of these types of spaces, it is necessary to know how to take care of them, so that they preserve their natural essence. The pathway was made up of sections that cross private and public properties, which was a difficulty that was solved through the proposal of a new delimitation of Parque Nacional Sangay, defining the path as a public space. In order to raise this proposal, the design of a natural axis was made, composed of its infrastructure and 2 architectural elements that correspond to the needs that are present in the place, the project aims at the conservation and care of the species, while the public space promotes free access to a protected area. Similarly, a restructuring of the existing ranger equipment at the beginning of the trail is proposed, to create a meeting place between the inhabitants and visitors and as a point of information and training for the ascent; in addition, equipment is proposed to monitor the possible risks analysed through a disaster control system for natural phenomena, located in the high mountain at 4140 m above sea level compared to the trail which is at 3860 m above sea level. It is recommended to consider the irregularity in the topography of the place in case of planning future projects that contribute to the development of the site and its surroundings, and the environmental impact in protected areas such as this one.